KETERLIBATAN GERAKAN SEPARATISME DALAM UPAYA KEMERDEKAAN CATALONIA DARI SPANYOL - Widodo, Agus; Nugrahani, Henny Saptatia Drajati (UI Scholars Hub, 2022)
The aim of the research is to find out the factors that caused the failure of the separatist movement to liberate the autonomous region of Catalonia from Spain, as well as to explain the defense-security strategy carried out by the Spanish government to maintain Catalonia as an inseparable part of this country. The researcher conducts an analysis based on two research questions: why the separatist movement failed to liberate Catalonia from Spain and what defense-security strategy the Spanish government did to defend Catalonia. The method used in this study is a qualitative method by processing primary data in the form of interviews with selected sources. In this study the Separatism Concept and Securitization Theory are used as the basis for researchers in conducting analysis. The findings of this study are as follows: first, the Catalan community is an important factor why the separatist movement failed to liberate Catalonia from Spain, even though it was through a referendum. The number of Catalonian people's participation in the referendum did not reach 50% of the total voter turnout. The next factor is the European Union which is firmly in the position of rejecting the existence of separatism in Catalonia which encourages the involvement of this autonomous region from Spain, which is a member state of the European Union. The second finding is the result of the analysis that the Spanish government has succeeded in carrying out a defense and security strategy through several decisive actions, namely the dissolution of the Catalan parliament, the takeover of the autonomous government of Catalonia, and holding elections for the election of the new Catalonia parliament which is considered to have been dominated by the separatist movement.